The Role of Ethylene in the Senescence of Oat Leaves - Gepstein, Shimon (1981)
The evolution of ethylene, both from the endogenous source and from added 1-aminocyclopropane-1-carboxylic acid (ACC), has been followed in close relationship with the senescent loss of chlorophyll from seedling oat leaves. In white light, where chlorophyll loss is slow, the ethylene evolution increases slowly at first, but when the loss of chlorophyll becomes more rapid, ethylene evolution accelerates. CoCl(2) inhibits this increase and correspondingly maintains the chlorophyll content, with an optimum concentration of 10 micromolar. The rapid rate of chlorophyll loss in the dark is slightly decreased by 3-aminoethoxyvinyl glycine (AVG), by cobalt, and slightly stimulated by ACC. The slower chlorophyll loss in white light, however, is almost completely inhibited by silver ions, greatly decreased by cobalt and by AVG, and strongly increased by ACC. Since the chlorophyll loss is accompanied by proteolysis, it represents true senescence. Chlorophyll loss in light is also strongly antagonized by CO(2), 1% CO(2) giving almost 50% chlorophyll maintenance in controls, while in the presence of added ACC or ethylene gas, the chlorophyll loss is 50% reversed by about 3% CO(2). The ethylene system in leaves is thus more sensitive to CO(2) than that in fruits. Indoleacetic acid also clearly decreases the effect of ACC. It is shown that kinetin, CO(2), Ag(+), and indoleacetic acid, all of which oppose the effect of ethylene, nevertheless increase the evolution of ethylene by the leaves, and it is suggested that ethylene evolution may, in many instances, mean that its hormonal metabolism is being prevented. Abscisic acid somewhat increases ethylene evolution also, but its action in promoting senescence in light is antagonized only partially by Ag(+), Co(2+), or AVG. For this and a number of other reasons it is concluded that ethylene and abscisic acid both independently control leaf senescence in the light.